FIGMA SITES AS A RESPONSIVE WEB DESIGN SOLUTION: AN ANALYSIS OF PRODUCTIVITY AND VISUAL CONSISTENCY IN DIGITAL DESIGN PRACTICE - Rahma, Nur Muthia (PERCIPIENCE International Journal of Social, Administration, & Entrepreneurship, 2024)
In the increasingly dynamic digital era, the need for responsive, efficient, and consistent web design has become crucial. Figma Sites, the latest feature of the Figma platform, offers a visual-first approach that integrates the design, prototyping, and publishing processes within a single, cloud-based collaborative ecosystem. This study aims to analyze Figma Sites' contribution to increasing designer productivity and maintaining visual consistency in digital interface development. Using a qualitative approach based on literature, data was reviewed from scientific articles, professional publications, and documentation of UI/UX design industry practices. The analysis results show that Figma Sites can reduce design iteration time, strengthen cross-functional coordination, and maintain uniformity of visual elements through the use of integrated design components and design systems. This study concludes that Figma Sites not only technically addresses modern design challenges but also offers an efficient collaborative work model in the context of digital transformation.